Respiratory virus modulation of host nucleocytoplasmic transport; target for therapeutic intervention? - Caly, Leon; Ghildyal, Reena; Jans, David A. (Frontiers in Microbiology, 2015)
The respiratory diseases caused by rhinovirus, respiratory syncytial virus, and influenza virus represent a large social and financial burden on healthcare worldwide. Although all three viruses have distinctly unique properties in terms of infection and replication, they share the ability to exploit/manipulate the host-cell nucleocytoplasmic transport system in order to replicate effectively and efficiently. This review outlines the various ways in which infection by these viruses impacts on the host nucleocytoplasmic transport system, and examples where inhibition thereof in turn decreases viral replication. The highly conserved nature of the nucleocytoplasmic transport system and the viral proteins that interact with it make this virus–host interface a prime candidate for the development of specific antiviral therapeutics in the future.